ENT300 Akbar Burger Restaurant / Nurfatin Athirah Mohd Azman... [et al.] - Mohd Azman, Nurfatin Athirah; Ricky Nelson Libau, Richealsea Rixxy Libau; Mohamad Zainudin, Nurdayana Sabreena; Lading, Dorinna Ritie; Syed Abdullah, Syed Muhammad Radzi (2016)
The form of the business is partnership. It is collaboration among our members to form or come out with a business. AKBAR BURGER consists of 4 members all together and each of us will contribute in term of capital with a certain amount as agreed in the agreement. Our business will start operating in 1st January 2017.